From New Women to College Girls at the Huguenot Seminary and College, 1895-1910 (Historia, 2021)
EnglishThe Huguenot Seminary was established in Wellington in 1874 by Andrew Murray with the aim of training middle-class Dutch-Afrikaans girls as teachers and missionaries. It was modelled along the lines of the American Mount Holyoke Seminary, which was also founded to provide an academic and religious education to young women. The Huguenot Seminary proved to be an enormous success and its associated College – founded in 1898 – was one of the first institutions in South Africa at which women could study for university degrees. Little has been written about the impact of the education provided at Huguenot – the school of choice for the daughters of the Cape DutchAfrikaans bourgeoisie – on notions of “femininity” within middle-class Dutch-Afrikaans society during the late nineteenth and early twentieth centuries. Seeking to address this lacuna, this article explores the discourses surrounding the ideal of the educated woman that arose at Huguenot between 1895 and 1910, particularly as portrayed in the institution’s annuals. These publications provide an insight into the girls’ perspectives on their education, as expressed in a number of conflicting and complimentary discourses on femininity, each of them attempting to engage with the ideal of the educated middle-class woman at the turn of the century.   AfrikaansVan New Women tot College Girls aan die Hugenote-seminarie en -kollege, 1895-1910 Die Hugenote-seminarie is in 1874 deur Andrew Murray in Wellington gestig met die doel om Hollands-Afrikaanse meisies uit die middelstand as onderwyseresse en sendelinge op te lei. Dit is geskoei op die voorbeeld van die Mount Holyoke-seminarie in die Verenigde State van Amerika, wat insgelyks gestig is om ŉ akademiese en Christelike opvoeding aan jong dames te voorsien. Die Hugenote-seminarie was uiteindelik ŉ reuse sukses en sy assosiaat, die Hugenote-kollege (wat in 1898 gestig is) was een van die eerste instellings in Suid-Afrika waar vroue universiteitsgrade kon behaal. Die Hugenote-seminarie en -kollege was die instellings van voorkeur vir dogters van die Kaap se Hollands-Afrikaanse bourgeoisie. Min is tot op hede geskryf oor die impak van die opleiding, wat gedurende die laat negentiende en vroeë twintigste eeu aldaar aangebied is, op idees oor “vroulikheid” binne hierdie middelstand gemeenskap. Ten einde die leemte aan te vul, ondersoek hierdie artikel die redevoering omtrent die ideaal van die geleerde vrou wat tussen 1895 en 1910 aan die instellings plaasgevind het, veral aan die hand van die Hugenotejaarboeke. Hierdie publikasies bied insig in die meisies se perspektiewe op hulle geleerdheid, soos uitgedruk in ŉ aantal uiteenlopende, asook komplimenterende argumente oor vroulikheid, wat almal die ideaal van die geleerde middelstand vrou tydens die era om die draai van die eeu aanspreek.
Keywords: Afrikaner; Andrew Murray; College Girl; education; femininity; girls; Huguenot College; Huguenot Seminary; middle class; New Woman; teachers; Hugenote-kollege; Hugenoteseminarie; meisies; middelklas; onderwyseresse; opvoeding; vroulikheid